Breeding new seedless table grapevines for a more sustainable viticulture in Mediterranean climate - Piarulli, Luciana; Pirolo, Costantino; Roseti, Vincenzo; Bellin, Diana; Mascio, Isabella; La Notte, Pierfederico; Montemurro, Cinzia; Miazzi, Monica Marilena (Frontiers in Plant Science, 2024)
The growing demand for sustainable and environmentally friendly viticulture is leading to a multiplication of breeding programs aimed at obtaining vines that are resistant to powdery mildew (PM) and downy mildew (DM), the two most damaging vine diseases. In Puglia, the most important Italian region for the production of table grapes, an extensive crossing program was launched in 2015 with 113 crosses, including elite table varieties, seedless varieties, and resistant varieties. The main seedling production parameters were measured for each cross. In particular, berries harvested as well as the number of seeds and seedlings obtained were considered. Approximately 103,119 seedlings were obtained and subjected to marker-assisted selection for seedlessness using the marker VvAGL11 and for resistance to PM and DM with appropriate markers. Approximately one third (32,638) of the progenies were selected as putative seedless and seventeen thousand five hundred-nine (17,509) were transferred to the field for phenotypic evaluation, including 527 seedless individuals putatively resistant, of which 208 confirmed to be resistant to DM, 22 resistant to PM, and 20 individuals that combined resistance and seedlessness traits. The work discusses the effects of parental combinations and other variables in obtaining surviving progeny and pyramiding genes in table grapes and provides useful information for selecting genotypes and increasing the efficiency of breeding programs for seedless disease-resistant grapes.